Methylenetetrahydrofolate Reductase Gene rs1801133 and rs1801131 Polymorphisms and Essential Hypertension Risk: A Comprehensive Analysis - Yingchao Fan; Liting Wu; Wenfang Zhuang (Cardiovascular Therapeutics)
Background. Essential hypertension (EH) is a common and multifactorial disorder that is likely to be influenced by multiple genes. The methylenetetrahydrofolate reductase (MTHFR) gene rs1801133 and rs1801131 polymorphisms influence MTHFR enzyme activity and plasma homocysteine concentration. In addition, variations in MTHFR functions likely play roles in the etiology of EH. Thus far, a large number of studies investigating the associations between the MTHFR polymorphisms and EH have provided controversial or inconclusive results. To better assess the purported relationship, we performed a comprehensive analysis of 52 published studies. Objective and Methods. Eligible studies were identified by searching the PubMed, Wanfang, and China National Knowledge Infrastructure (CNKI) databases. Odds ratios (ORs) with 95% confidence intervals (CIs) were estimated to assess the potential association between the MTHFR rs1801133 polymorphism and EH. Results. Overall, 10712 patients and 11916 controls were involved; we observed significantly increased association between the MTHFR rs1801133 polymorphism and EH risk (such as T vs. C: OR=1.38, 95% CI=1.25−1.54, P≤0.001), with similar results evident within race subgroups (such as Asian: T vs. C: OR=1.47, 95% CI=1.30−1.67, P≤0.001; compared to Chinese: T vs. C: OR=1.54, 95% CI=1.33−1.79, P≤0.001). Similar associations were also found in subgroups defined by the source of controls and genotype methods. To our regret, based on the limited studies, no association was detected for rs1801131 polymorphism. Conclusions. Our study provides evidence that the MTHFR rs1801133 null genotype may increase EH risk. Future studies with larger sample sizes are warranted to evaluate this association in more detail.